A Description of Trainer's Personality Competence at the Red Cross Extracurricular Program at SMA Negeri 8 Padang - Sudarlisno Purwanto; Jalius Jalius (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2022)
This research was motivated by the high activity of students in the Youth Red Cross (PMR) extracurricular program at SMA Negeri 8 Padang. This study describes the personality competence of coaches in the Youth Red Cross (PMR) extracurricular program at SMA Negeri 8 Padang. this is based on the trainer's approach and application of students when carrying out training, and the trainer also shows appropriate attitudes and training methods. The aims of this research are (1) to describe the Personality Competence of the Trainer as a Person Who Acts According to Norms. (2) Describe the Instructor's Personality Competence as an Honest, Noble Person. (3) Describe the Instructor's Personality Competence Presenting Himself as a Steady Person. (4) Describe the Instructor's Personality Competence in Demonstrating a High Work Ethic.This research is a research with a quantitative approach and this type of research is descriptive. The population in this study were 30 people, the sampling technique was Stratified Random Sampling with a sample of 20 people. Techniques for collecting data using questionnaires and data collection tools in the form of a list of statements. Data analysis techniques use the percentage formula.The results of this study indicate that: (1) the description of the trainer's personality competence acting in accordance with the norms is categorized as very high. (2) the description of the trainer's personality competence presenting himself as an honest and noble person is categorized as very high. (3) the description of the trainer's personality competence presents himself as a stable person who is categorized as very high. (4) the description of the trainer's personality competence shows that the work ethic is categorized as very high. It is hoped that Padang 8 Public High School will always innovate in improving extracurricular activities, especially the Youth Red Cross (PMR) extracurricular so as to attract students' interest in joining extracurricular activities. To trainers to always support and improve training activities so as to support quality and quantity in the implementation of training.Keywords: Personality Competence, Ekatracurricular